New Trends in Humanitarian Assistance – Enticing the Private Sector : The Value Chain Approach - Montesclaros, Jose (2018)
Since the Sulawesi quake and tsunami, ASEAN member states have agreed to increase financial contributions to Humanitarian Assistance and Disaster Relief (HADR) operations. However, an alternative framing of HADR is needed to draw enterprises in bridging gaps.